Long-distance vector Brillouin optical time-domain analysis sensors using distributed Brillouin amplification with frequency-comb pump parallel demodulation. (21st October 2020) - Xu, Shi-Rong; Ma, Hui-Liang; Jia, Xin-Hong; Lin, Jia-Bing; Yang, Yu-Lian; Liang, Wen-Yan
Abstract: We demonstrated a structure for extending repeater-less sensing distance of Brillouin optical time-domain analysis enhanced by distributed Brillouin amplification (DBA-BOTDA) through a combination with the Brillouin phase spectrum (BPS), where parallel demodulation of the frequency-comb pump can be realized. The careful structure design is implemented to perfectly suppress the impacts of various phase noises on long-distance BPS extraction. ∼98.9 km sensing distance and ∼6.5 m spatial resolution were demonstrated, with only four times frequency sweeping. The standard deviation of Brillouin frequency shift can be decreased to within ∼2 MHz by a combination of Brillouin gain spectrum and BPS.